Kualitas Pelayanan Di CV. Sukses Jaya Abadi - Vierra Chandra; Hengky Kosasih (Yayasan Literasi Sains Indonesia, 2022)
This article discusses the Quality of Service at CV. Eternal Success. CV. Sukses Jaya Abadi is a place that sells building materials. The purpose of this research is to find out how the service to customers at CV. Eternal Success. There are eight dimensions of quality that can be done in strategic planning and analysis, namely performance, additional features and characteristics, reliability, conformance to specifications, durability, serviceability, aesthetics, perceived quality (service quality) Gavin Dalam Tjiptono, 2021. In carrying out this research, the author uses descriptive qualitative research methods. The sample of this research is customers at CV. Success Jaya Abadi, totaling 10 people. Sampling using purposive sampling technique, the technique of determining the sample is based on structured interviews, namely detailed interviews which are almost the same as questionnaires. The results of this study indicate that the factor that is considered by the customer is honesty. The second product is sold well enough so that buyers are satisfied. The third is the problem of lack of transportation, which hinders customers who want their goods to be delivered quickly. The fourth ability in serving is considered quite good and makes consumers feel more valued and cared for indirectly. Therefore CV. Success Jaya Abadi needs a little improvement to be better than before.